IDENTIFIKASI PENILAIAN BANGUNAN GEDUNG RUMAH SAKIT TERHADAP PENERAPAN KONSEPRUMAH SAKIT RAMAH LINGKUNGAN - Alfa Nur Alim; Darmawan Pontan (Jurusan Arsitektur Fakultas Teknik Sipil dan Perencanaan Universitas Trisakti, 2024)
The aims of the study is to determine the results of the assessment of hospital buildings based onthe Greenship Existing Building Version 1.1 indicator from the Green Building Council Indonesia(GBCI) and environmentally friendly hospital guidelines from the Ministry of Health of the Republicof Indonesia in 2018. The method used in this study is descriptive qualitative with data collectionthrough observation, interviews, documentation and measurements carried out continuously fromthe beginning of the research implementation and during the research process. With this research,hospital managers can know about the extent of the assessment of the application of environmentallyfriendly hospitals so that the results of this study can be used as a reference in the application ofgreen buildings and green hospitals in Indonesia. Keywords : Green Building, Green Hospital, Greenship Existing Building, Green Building Council